A Transitivity Analysis of the Experience of Depression as Expressed on Thai Twitter - Klaisingto, Pennapa (Journal of Liberal Arts Prince of Songkla University, 2021)
Twitter is an online platform where users can express their experiences and opinions. Depression is conveyed on Twitter through a writer’s point of view. Transitivity analysis examines the verbal choices a speaker or writer makes to reflect their view of a given situation. This study focused on a transitivity analysis of the experience of depression as seen on Thai Twitter. Transitivity was analyzed in 200 tweets (Twitter messages) with the hashtags #ซึมเศร้า [sµmsaßw] (#depression) and #โรคซึมเศร้า [roßoksµmsaßw](#depressivedisorder). The analysis focused on the types of processes represented in the tweets, with the results demonstrating six such processes: mental, behavioral, material, existential, relational, and verbal. In the 200 tweets examined, 642 verbs were present. The most frequent type of process found was mental (38.94%), followed by behavioral (26.79%), material (12.62%), relational (7.63%), verbal (7.17%), and existential (6.85%). The results indicate that mental processes were found most frequently to represent negative feelings in various words and phrases such as want to cry, upset, and painful; for behavioral processes, cry and unintentionally laughing on the outside; for material processes, destroyed and used to be bullied; for existential processes, to exist; and for verbal processes, beg and complain. This transitivity analysis reflects the experience of depression as it is expressed on Twitter. The verbal choices in these tweets can function as indicators of depressive disorder.